2021
DOI: 10.1038/s41598-021-85573-z
|View full text |Cite
|
Sign up to set email alerts
|

Normal weight obesity and the risk of diabetes in Chinese people: a 9-year population-based cohort study

Abstract: We evaluated the risk of developing diabetes in Chinese individuals with normal weight obesity (NWO). This 9-year population-based cohort study was based on the China National Diabetes and Metabolic Disorders Survey. A total of 1128 subjects without diabetes were included. Body fat percentage (BF%) was assessed by electrical bioimpedance. NWO was defined as subjects with a normal BMI (< 24 kg/m2) and an excess BF% (≥ 24% in men; ≥ 33% in women). Of 1128 individuals, 528 individuals were normal weight non-ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…In our meta‐analysis, the NWO group was significantly associated with DM, higher levels of fasting, 2 h post‐prandial plasma glucose, HbA1c and fasting insulin. Consistently, a longitudinal cohort study showed that NWO increases the risk of DM 57 …”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In our meta‐analysis, the NWO group was significantly associated with DM, higher levels of fasting, 2 h post‐prandial plasma glucose, HbA1c and fasting insulin. Consistently, a longitudinal cohort study showed that NWO increases the risk of DM 57 …”
Section: Discussionmentioning
confidence: 58%
“…Consistently, a longitudinal cohort study showed that NWO increases the risk of DM. 57 Regarding hypertension in the NWO group, several pathological mechanisms are considered responsible. 58 Systemic inflammation related to obesity could induce vasoconstriction through the vascular endothelium's reduced nitric oxide (NO) production.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous review [ 24 , 25 , 31 48 ] and our current study [ 22 , 23 , 30 ], the following variables were considered candidate predictors to judge a patient with or without metabolism: age, sex, education level, smoking history, physical activity history, family history of metabolic disorders (abbreviated as family history), SBP, DBP, WC, HC, WHR, WHtR, BRI, BMI, PBF, ABSI, CUN_BAE, BAI, C-Index, and AVI.…”
Section: Methodsmentioning
confidence: 93%
“…A total of 1072 participants were included in phase 3 follow-up surveys. Relevant information on the dataset can be found in our previous studies [ 22 , 23 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation